Carbide Tool Wear Analysis for Manufacturing Aisi 4140 Alloy Steel with 2D/3D Deform Simulation in PT Rejeki Sekawan Abadi - Bayu Susilo; Anis Siti Nurrohkayati (Procedia of Engineering and Life Science, 2022)
The lathe process is a machining process that is most widely used and is very commonly used in an industrial field. During the turning process, the lathe will cut the workpiece with the main movement being rotating so that the workpiece can be slowly reduced in diameter. There are several parameters in the turning process such as feed rate, cutting speed and cutting depth. Parameter optimization in the cutting process is very necessary in order to reduce the cutting force during the machining process. If the cutting force is high, it can cause the tool ability to be reduced. In this study using three turning parameters, namely spindle rotation rate, feeding depth, and feed or chisel distance in 1 rotation of the workpiece. This can be seen from the simulation results, the results of simulation-2 and simulation-4 with a feed rate of 0.1 mm/rad with two other different parameters, the value of the depth of tool wear is 0.00487 and 0.00410 mm, then in simulation-1 and simulation -3 with the same feed rate value of 0.2 mm/rad and with two other different parameters, the depth of tool wear is 0.0117 and 0.00932 mm, respectively. With these results, it can be seen that the feed rate has quite an effect on the depth of tool wear during the turning process. Based on the results of the study, it can be concluded that the variation of the parameters that are simulated in the turning process can affect the condition of the tool blade used. When running the machining process with inappropriate parameters, it will cause tool failure or tool blade damage. Therefore, the lathe parameters must be considered.